A review of thiocyanate gold leaching – Chemistry, thermodynamics, kinetics and processing - Azizitorghabeh, Atefeh; Wang, Jingxiu; Ramsay, Juliana A.; Ghahreman, Ahmad (Minerals engineering, 2021)
[Display omitted] •Gold leaching by thiocyanate as a promising less toxic lixiviant than cyanide.•Thiocyanate resonances and its coordination with gold using Infrared spectroscopy were investigated.•Effective parameters on thermodynamics and kinetics of thiocyanate gold leaching were studied.•Optimum condition of gold leaching using thiocyanate was evaluated.•Gold recovery processes from pregnant leach solution were summarized. Thiocyanate is among the most promising alternative gold lixiviants for gold leaching and has not been extensively covered in the literature. Thiocyanate is 1000 times less toxic than cyanide and is a very strong gold leaching lixiviant. This review paper provides an overview of the chemistry, thermodynamics, kinetics, and processing of gold leaching using thiocyanate as well as gold recovery from the pregnant leach solution. One main reason that the thiocyanate gold leaching process has not yet been commercialized is that the process requires a reduction-oxidation (redox) potential higher than that required of cyanide gold leaching. The oxidant, mostly ferric, is needed to leach gold. However, the redox potential must be lowered by removing oxidants to allow gold recovery from the pregnant leach solution. The molar ratio of oxidant to thiocyanate is considered an effective parameter for gold oxidation kinetics and should range between 2 and 20. Thiocyanate gold leaching is an electrochemical reaction which occurs at pH 1.5–2.5 and electrochemical potential of 600–700 mV. The literature shows fast gold leaching kinetics in well-designed thiocyanate systems. The solubilized gold-thiocyanate species can be recovered from the pregnant leach solution by a variety of methods including conventional activated carbon adsorption, solvent extraction, ion exchange, and cementation. Leaching can be performed in both heaps and tanks.